Performances of electrodialysis process in desalination of brackish waters at various salinities and voltage - Fatima, Elazhar; Elazhar, Maryem; Hafsi, Mahmoud; Elmidaoui, Azzeddine (International Journal of Advanced Chemistry, 2014)
In the south Mediterranean countries and especially the North Africa, the water demands, since many decades, have increased while the conventional water availability has decreased dramatically. These trends continue. The obligation to use other non-conventional water resources such as desalinating water or waste water reuse becomes a necessity. Electrodialysis is a membrane process that competes with reverse osmosis for desalination and the removal of specific inorganic contaminants The experiments for desalination were carried out of various synthetic brackish waters containing 2, 4, 6, 8 and 10 g/l NaCl in order to determinate the operating conditions of electrodialysis process. The pilot used supplied by the Tokuyama Corp. The influence on the desalination performances of many running parameters such as voltage and salinities was investigated. These studies demonstrated that the electrodialysis is an effective method of being used to desalinate brackish water was well as water with higher salt concentrations up to about 10 g/L NaCl.   Keywords: Electrodialysis, Performances, Membrane, Voltage, Salinities, Intensity.